5PSQ-188 An audit of prescribing, administration and storage of concentrated electrolytes. (14th March 2021) - Beakey, A; Holacka, K; Kieran, M; Brown, J
Abstract : Background and importance: Concentrated electrolytes can be fatal if administered inappropriately. Local hospital policies and protocols exist to ensure appropriate concentrated electrolyte treatment for patients, while reducing the risk of inappropriate or incorrect administration. Patient safety is optimised by using ready mixed bags where possible and ensuring correct storage of intravenous (IV) electrolytes, both concentrated electrolyte ampoules and non-concentrated ready mixed bags, at ward level to reduce the risk of mis-selection and drug error. Local incident reports indicated poor compliance with hospital concentrated electrolyte policies and protocols and so an audit was undertaken to assess this. Aim and objectives: This study aimed to audit the prescribing, administration and storage of concentrated electrolytes in a large teaching hospital. Material and methods: Adherence to hospital concentrated electrolyte protocols and guidelines was determined by a point prevalence audit undertaken in February 2019. Data were collected by clinical pharmacists on a single day and included review of prescriptions from the preceding 7 days. Results: There were 133 prescriptions for IV electrolytes on 14 wards. Prescribing and administration was appropriate in 32% (n=43) of cases. Appropriate storage of concentrated electrolyte ampoules was noted on 95% of the wards. Segregated storage of ready mixed electrolyte bags was found on 30% of the wards. Of the 94 potassium chloride prescriptions, ampoules were administered in 78% (n=73) of cases and ready mixed bags were administered in 21% (n=20) of cases. No inappropriate use was identified; however, in 43% (n=31) of cases, no diluent or volume was specified and therefore it was unclear if use of ampoules was clinically indicated. These instances were due to 'as required' prescribing of concentrated electrolytes in the cardiothoracic patient cohort, which requires follow–up. The Drug Safety Service analysed and circulated the audit results to pharmacy, nursing and medical staff to highlight the main findings and recommendations. Conclusion and relevance: A number of improvement areas were identified: Complete concentrated electrolyte prescriptions in accordance with hospital protocols, avoiding 'as required' incomplete prescriptions. Define parameters for IV electrolyte replacement postoperatively in cardiothoracic patients. More clearly define 'segregated storage' of ready mixed potassium chloride bags. Re–audit; undertaken in July 2020, the results of which are currently being analysed. References and/or acknowledgements: Conflict of interest: No conflict of interest